Environmental conservation efforts for disaster mitigation based on local wisdom in Colo Dawe - Zubair, Abi Amar; Muhammad Nur, Dany Miftah (JIPSINDO, 2024)
Geographical conditions may promote a potential for natural disasters in every region. The research aims to investigate: 1) the efforts and implementation of environmental conservation for local wisdom-based disaster mitigation in Colo Dawe Kudus, and 2) the achievements of environmental conservation efforts for local wisdom-based disaster mitigation in Colo Dawe, Kudus. This research used a qualitative descriptive approach with an ethnographic design. Data collection was done through observation, interviews, and documentation. The research results showed that Colo Village is located on a plateau that can potentially experience landslides. The Colo community uses the cultural approach for disaster mitigation. The local wisdom of the Colo people is considered capable of preserving the environment through rituals, including the Wiwit Kopi, Sedekah Bumi, Sewu Kupat,  and Guyang Cekathak traditions. Using cultural approaches in Colo Village, disaster mitigation efforts include natural landslide disasters and other hydrometeorological disasters, such as drought disaster mitigation efforts. This research contributes to social science's development, especially in sociology, anthropology, and geography.